Vascular Endothelial Growth Factor in Tear Samples of Patients with Systemic Sclerosis - Anikó Rentka; Jolán Hársfalvi; András Berta; Krisztina Köröskényi; Zoltán Szekanecz; Gabriella Szücs; Peter Szodoray; Ádám Kemény-Beke (Hindawi Limited, 2015)
Background. Systemic sclerosis is an autoimmune disease, characterized by widespread small vessel vasculopathy, immune dysregulation with production of autoantibodies, and progressive fibrosis. Changes in levels of proangiogenic cytokines had already been determined largely in serum. Our aim was to assess the levels of VEGF in human tears of patients with SSC. Patients and methods. Forty-three patients (40 female and 3 men, mean (SD) age 61 (48-74) years) with SSc and 27 healthy controls were enrolled in this study. Basal tear sample collection and tear velocity investigations were carried out followed by an ophthalmological examination. Total protein concentrations and VEGF levels were determined in tear samples. Results. The average collected tear fluid volume developed 10.4 μL (1.6-31.2) in patients and 15.63 μL (3.68-34.5) in control subjects. The average total protein level was 6.9 μg/μL (1.8-12.3) in tears of patients and control tears contained an average of 4.132 μg/μL (0.1-14.1) protein. In patients with SSc the average concentration of VEGF was 4.9 pg/μL (3.5-8.1) and 6.15 pg/μL (3.84-12.3) in healthy samples. Conclusions. Total protein production was increased because of the smaller tear volume. Decreased VEGF in tear of SSc patients can be explained also by the decreased tear secretion of patients.